Breast cancer screening among Hispanic and non‐Hispanic White women by birthplace in the Sister Study. (12th February 2022) - Talham, Charlotte J.; Montiel Ishino, Francisco A.; O'Brien, Katie M.; Sandler, Dale P.; Williams, Faustine
Abstract: Background: Hispanic/Latina women are less likely to be diagnosed with local stage breast cancer than White women. Additionally, foreign‐born women have lower mammography rates than US‐born women. We evaluated the combined effect of birthplace and race/ethnicity on screening habits of women at higher‐than‐average risk of breast cancer. Methods: Multinomial logistic regression was used to evaluate breast cancer screening in 44, 524 women in the Sister Study cohort. Screening methods ascertained at enrollment (2003–2009) included mammography, ultrasound, and magnetic resonance imaging. Timing of screening was assessed as recently (≤2 years ago), formerly (>2 years ago), and never screened. Adjustments included sociodemographic, socioeconomic, and health variables. Results: Most women in the sample were US‐born non‐Hispanic/Latina White (92%), were ≥50 years old (73%), had one first‐degree female relative with breast cancer (73%), and were screened in the past two years (97%). US‐born Hispanic/Latina women had higher odds (odds ratio [OR] = 1.47, 95% confidence interval [CI] = 1.08–2.00) than US‐born non‐Hispanic/Latina White women of not having received a breast cancer screening in the past 2 years, relative to a recent screening. Similarly, foreign‐born Hispanic/Latina women had higher odds (OR = 1.63, 95% CI = 1.10–2.41) than US‐born non‐Hispanic/Latina White women of never having received a breast cancer screening. Conclusion: We observed that Hispanic/Latina women have higher odds of never and dated breast cancer screenings compared to US‐born White women. Birthplace and race/ethnicity each contribute to disparities in who receives preventative health care in the United States. It is critical to include birthplace when evaluating health behaviors in minority groups. Abstract : Multinomial logistic regression was conducted on 44, 524 Hispanic and non‐Hispanic White women from the Sister Study cohort to evaluate the associations between combined birthplace and race/ethnicity and timing of most recent breast cancer screening, while controlling for sociodemographic, socioeconomic, and health factors. Foreign‐born Hispanic women were found to have higher odds of never receiving a breast cancer screening compared to US‐born non‐Hispanic White women. Similarly, US‐born Hispanic women were found to have higher odds of having an outdated breast screening compared to US‐born non‐Hispanic White women.